Industry Structure, Executive Pay, and Short-Termism - Thanassoulis, John (Management Science, 2013)
This study outlines a new theory linking industry structure to optimal employment contracts and executive short-termism. Firms hire their executives using optimal contracts derived within a competitive labour market. To motivate effort, firms must use some variable remuneration. Such remuneration introduces a myopia problem: an executive would wish to inflate early expected earnings at some risk to future profits. To manage this short-termism, some bonus pay is deferred. Convergence in size among firms makes the cost of managing the myopia problem grow faster than the cost of managing the effort problem. Eventually, the optimal contract jumps from one deterring myopia to one tolerating myopia. Under some conditions, the industry partitions: the largest firms hire executives on contracts tolerant of myopia; smaller firms ensure myopia is ruled out. This paper was accepted by Wei Xiong, finance.